COPD exacerbation severity and frequency is associated with impaired macrophage efferocytosis of eosinophils - Eltboli, O; Bafadhel, M; Hollins, F; Wright, A; Hargadon, B; Kulkarni, N; Brightling, C (BioMed Central, 2014)
Background: Eosinophilic airway inflammation is observed in 10-30% of COPD subjects. Whether increased eosinophils or impairment in their clearance by macrophages is associated with the severity and frequency of exacerbations is unknown. Methods: We categorised 103 COPD subjects into 4 groups determined by the upper limit of normal for their cytoplasmic macrophage red hue (<6%), an indirect measure of macrophage efferocytosis of eosinophils, and area under the curve sputum eosinophil count (≥3%/year). Eosinophil efferocytosis by monocyte-derived macrophages was studied in 17 COPD subjects and 8 normal controls. Results: There were no differences in baseline lung function, health status or exacerbation frequency between the groups: A-low red hue, high sputum eosinophils (n = 10), B-high red hue, high sputum eosinophils (n = 16), C-low red hue, low sputum eosinophils (n = 19) and D- high red hue, low sputum eosinophils (n = 58). Positive bacterial culture was lower in groups A (10%) and B (6%) compared to C (44%) and D (21%) (p = 0.01). The fall in FEV1 from stable to exacerbation was greatest in group A (ΔFEV1 [95 % CI] -0.41 L [-0.65 to -0.17]) versus group B (-0.16 L [-0.32 to -0.011]), C (-0.11 L [-0.23 to -0.002]) and D (-0.16 L [-0.22 to -0.10]; p = 0.02). Macrophage efferocytosis of eosinophils was impaired in COPD versus controls (86 [75 to 92]% versus 93 [88 to 96]%; p = 0.028); was most marked in group A (71 [70 to 84]%; p = 0.0295) and was inversely correlated with exacerbation frequency (r = -0.63; p = 0.006). Conclusions: Macrophage efferocytosis of eosinophils is impaired in COPD and is related to the severity and frequency of COPD exacerbations.